Public relations professionals’ communication strategies in responding the COVID-19 pandemic based on gender - Santoso, Nobertus Ribut (Plaridel, 2021)
Access online through this link: https://www.plarideljournal.org/article/public-relations-professionals-communication-strategies-in-responding-the-covid-19-pandemic-based-on-gender